"I was prepared for the worst I guess": stayers' and leavers' perceptions of their Title IV-E education. Issue 3 (27th May 2018) - Benton, Amy D.; Iglesias, Michelle
ABSTRACT: Child welfare workforces across the nation are experiencing high turnover and have for decades. The chronic cost of turnover makes efforts to increase retention crucial. The Title IV-E education stipend program is one way that many states employ to improve their child welfare worker tenure. Through qualitative interviews, this study examines Title IV-E graduates' experiences and perceptions of preparedness for working in child welfare agencies. Examining how the responses of stayers and leavers differ and assessing similarities collectively can inform educational and agency enhancements to improve services, as well as worker competence and retention.